Pengalaman Remaja dalam Proses Kebangkitan dan Pemulihan Diri Setelah Mengalami Trauma Akibat Cyberbullying pada Era Digital - Sri Rahayu Ningsih; Muthi’ah Syifa Isnaini; Hidayati Ruslaini; Nurlaila Nasution; Khairani Syahfitri; Rahmayani Rahmayani (Jurnal Pendidikan Dirgantara, 2025)
Bullying is a recurring issue and has become a widespread concern, particularly among children and adolescents in school environments. Schools, which should ideally be safe spaces for learning, building friendships, and experiencing personal growth, often turn into places of fear and psychological distress for some students. This is largely due to the frequent violation of human rights (HR) that often goes unaddressed or is underestimated. Bullying can take many forms, including verbal, psychological, physical abuse, and increasingly, cyberbullying. Each of these forms can cause serious harm not only to the victims—who may suffer from emotional and mental trauma—but also to the perpetrators, who may experience long-term psychological consequences and develop deviant or aggressive behavior patterns. In Indonesia, bullying remains a significant issue and a major concern in the education sector. Nearly every school has faced incidents of bullying in one form or another. Cyberbullying, in particular, is harder to monitor and control since it often occurs outside the school’s jurisdiction and is carried out through social media platforms. Efforts to tackle bullying must go beyond merely protecting and supporting the victims. A comprehensive approach is necessary, one that also focuses on preventive education. Students, teachers, and parents must be consistently educated on the negative impacts of bullying, the importance of empathy, and a deeper understanding of human rights. Moreover, strict and clear sanctions must be imposed on perpetrators as a form of legal enforcement and deterrence. With a holistic strategy that involves all elements of the school and the wider community, it is hoped that educational institutions can truly become safe, inclusive, and supportive environments. Such conditions are essential for fostering not only academic growth but also the psychological well-being and character development of the nation's children.